THE MOON AND THE SUN AS LITERARY ARCHETYPES (International Congress on Economics, Management and Business Studies, 2026)
This article examines the nature of the images of the moon and the sun as literary archetypes, their mythological, philosophical, and aesthetic origins, and their functional-semantic potential in the literature of different periods. The concept of the archetype is interpreted on the basis of C. G. Jung‘s views on the collective unconscious and primordial images, as well as N. Frye’s theory of archetypal criticism. The study considers the moon and the sun not merely as landscape elements or poetic ornaments, but as archetypal images that shape the ideological and compositional system of a literary work and express such categories as the psychology and destiny of the protagonist, love, life and death, knowledge and ignorance, consciousness and the unconscious, time and eternity. Literary works featuring images of the moon and the sun are analyzed, and the semantics of their archetypal meanings are identified. At the same time, the study demonstrates that these meanings are neither fixed nor immutable in literary texts; rather, authors may invert, juxtapose, or individually reinterpret archetypal meanings within their own poetic systems. In particular, it is argued that in Frankenstein, the sun and the moon represent two different psychological dimensions of the archetype of light; in Romeo and Juliet, they embody the opposition between love and instability; in A Midsummer Night’s Dream, Sol and Luna express the relationships between consciousness and the unconscious, masculinity and femininity, order and transformation; in Moby-Dick, the sun functions as an ambivalent symbol of cosmic and divine power; while in Alisher Navoi’s epics, the moon and the sun represent beauty, perfection, and divine love within the framework of classical Eastern poetics.
Keywords: archetype, literary archetype, moon, sun, mythologeme, symbol, Jung, Frye, mythopoetics, light, darkness, love, fate, life, death, consciousness, unconsciousness, classical literature, modern literature.